An mRNA vaccine induces antimycobacterial immunity by activating DNA damage repair and autophagy - Dan Chen; Weili Huang; Lifang Shen; Junli Zhang; Zhifen Pan; Chen Zhang; Yuting Tang; Ziwei Zhou; Jie Tao; Geyang Luo; Shifeng Zhang; Jing Zhou; et al. (Molecular Therapy: Nucleic Acids)
Effective vaccines are urgently needed for the control of tuberculosis (TB). Here, we report that an mRNA TB vaccine is highly effective and exhibits both prophylactic and therapeutic activity in the zebrafish model of TB. Adult zebrafish immunized with the mRNA vaccine survived significantly longer after Mycobacterium marinum challenge compared to those immunized with the DNA vaccine. Furthermore, post-infection treatment with the mRNA vaccine drastically reduced the bacterial burden. The mRNA vaccine activated multiple DNA break repair systems that are essential for the normal development and function of adaptive immunity, but did not activate the canonical DNA damage responses that promote cell death. This highlights a profound connection between DNA damage repair and the activation of immune responses under physiological processes of immunization. Remarkably, the mRNA vaccine induced autophagy in granulomas, coinciding with bacterial killing and cell survival. Collectively, these findings demonstrate that the mRNA vaccine elicits potent innate and adaptive immunity, providing effective host protection against mycobacterial challenge.